Reconciling performance and predictability on a many-core through off-line mapping - Carle, Thomas; Djemal, Manel; Genius, Daniela; Pecheux, Francois; Potop Butucaru, Dumitru; de Simone, Robert; Wajsburt, Franck; Zhen Zhang (2014 9th International Symposium on Reconfigurable and Communication-Centric Systems-on-Chip (ReCoSoC), 2014)
We start from a general-purpose many-core architecture designed for average-case performance and ease of use. In particular, its distributed shared memory programming model allows the use of a code generation flow based on the (unmodified) gcc compiler chain. We modify this architecture and extend the code generation flow to allow the construction of efficient hard real-time systems starting from dependent task specifications. We rely on a static (off-line) real-time scheduling paradigm well-adapted to embedded control and signal processing applications with regular control structure. We modify the architecture (and in particular the on-chip network) to allow the implementation of static schedules with very high (clock cycle) temporal precision. On the software side, we define application mapping rules ensuring that the timing precision provided by the hardware is not lost. These mapping rules include requirements on the allocation of data variables to specific RAM banks and on the use of locks to ensure the absence of contentions during access to shared resources. Applications complying with these rules can be written manually or automatically obtained using a new mapping tool that takes all the allocation and scheduling decisions. Compilation of the resulting C code is still done using the (unmodified) gcc compiler chain. The resulting platform provides good performance, and at the same provides very high timing precision, as shown by two case studies (an embedded controller and an implementation of the FFT). We conclude our paper with a presentation of some ongoing work on the subject: A case study (an implementation of the H.264 decoder) meant to test the limitations of our method.